Early Childhood Learning in Spiritual Intelligence Development - Eka Riyanti; Mintarsih Arbarini; Kurotul Aeni (Indonesian Journal of Early Childhood Education Studies, 2024)
This study intends to analyze the implementation of early childhood learning in the development of spiritual intelligence and the benefits of developing spiritual intelligence for early childhood. Research place in Raudhatul Athfal Muslimat, Nahdlatul Ulama, Wonokerto, Kulon, Pekalongan regency, Central Java. This research uses a qualitative approach with a case study method. The subjects are teachers of groups A and B, children of groups A and B. Data collection techniques with observation, interviews and documentation with the validity of the data used are triangulation. Data analysis techniques with Milles and Hubberman models with steps namely data collection, data reduction, data presentation and conclusions. The results of this study are the implementation of learning in developing spiritual intelligence in Raudhatul Athfal Muslimat Nahdlatul Ulama Wonokerto Kulon, namely the development strategy applied integrated with the development of religious and moral values is by: 1) routine activities, namely teachers carry out daily habituation activities programmatically and consistently; 2) integrated activities, namely activities programmed with other areas of children's abilities; 3) Special activities, namely this program is carried out according to the needs and time available. The development of early childhood spiritual intelligence aims to provide early knowledge as a reminder and limitation in determining attitudes and actions with the support of parents, teachers and the community.